2001
DOI: 10.1016/s0029-7844(00)01111-x
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal outcome, placental pathology, and severity of discordance in monochorionic and dichorionic twins

Abstract: Severe discordance is more frequent and has greater morbidity in monochorionic than dichorionic twins. The most frequent findings in the placentas of severely discordant twins were small placental weight and umbilical cord abnormalities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
130
2
12

Year Published

2002
2002
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 167 publications
(156 citation statements)
references
References 17 publications
12
130
2
12
Order By: Relevance
“…Fetal thrombosis was associated with SGA, confirming the work of others. 6,7 Redline et al 8 reported that avascular villi with occlusion of fetal vessels in the placenta was associated with intrauterine growth retardation and discordant growth in monochorionic-twin placentas. Fetal vessel thrombosis is common in the placentas of SGA infants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fetal thrombosis was associated with SGA, confirming the work of others. 6,7 Redline et al 8 reported that avascular villi with occlusion of fetal vessels in the placenta was associated with intrauterine growth retardation and discordant growth in monochorionic-twin placentas. Fetal vessel thrombosis is common in the placentas of SGA infants.…”
Section: Discussionmentioning
confidence: 99%
“…Victoria et al 6 and Hanley et al 7 reported that severe discordance occurred significantly more often in monochorionic than in dichorionic twins and was significantly associated with velamentous cord insertions. Redline et al 8 demonstrated that peripheral insertion of the umbilical cord and avascular villi were associated with abnormal growth in twins.…”
mentioning
confidence: 99%
“…Discordancy was calculated using the intertwin birth weight difference expressed as a percentage of the larger twin's birth weight. 2,3,16,17 Discordancy equal to or greater than 20% separates concordant from discordant twins. Zygosity was determined prenatally by ultrasound and postnatally by placental examination.…”
Section: Methodsmentioning
confidence: 99%
“…18 TTTX was diagnosed in identical twins by discordance in fetal weight and ultrasonographic documentation of polyhydramnios in one and olygohydramnios in the other. 2,17,19 Significant differences in umbilical cord hemoglobin, which are indicative of acute but not of chronic TTTX, were not used as diagnostic criteria. 2 All ELBW infants were treated empirically with ampicillin (100 mg/kg per day IV given in two doses every 12 hours) and gentamicin (5 mg/kg/day IV given every 48 hours) for 2 days if blood cultures were negative.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation